Retrofitting of the NOx-02 analyzer and testing on the NO-CO-02 reaction over ceria-alumina. - Villaverde, Concepcion S. (Animo Repository, 1998)
The NOx-02 Analyzer (NOA-7000) acquired through the DOST-ESEP is retrofitted to make it functional in a flow reactor system used in catalyis work. An air inlet and moisture trap was connected to ensure that the sample gas meets the required specifications of the equipment.To measure the performance of the NOx-02 Analyzer retrofitted to adapt it to low gas flowrates involved in the flow reactor system also equipped with Gas Chromatography Apparatus, a preliminary activity test on the efficiency of ceria-alumina (CeO2 - Al2O3) as a catalyst in the NO-CO-O2 reaction was conducted. The catalyst was evaluated in terms of its activity against time, effect of temperature and the effect of CO partial pressure.Results showed that the ceria-alumina exhibited moderate activity for CO conversion but quite low for NO reduction in the presence of oxygen. The conversions of NO and CO, CO2 yield and O2 consumption increased as the reaction temperature is increased. Lastly, the study revealed that NO conversion is inversely proportional to the concentration of CO. While the CO conversion increased with CO concentration.